Gender Informed Monitoring and Evaluation in Disaster Risk Management - World Bank (World Bank, Washington, DC, 2017)
This note on gender informed monitoring and evaluation in disaster risk management is the third in a series of guidance notes on gender issues in disaster risk management (DRM) in East Asia and the Pacific. The note looks at the collection and analysis of sex-disaggregated data, needs assessments, pre- and post-disaster assessment and analysis, and gender indicators. Select references specific to gender and DRM are given at the end of this note. Good practice disaster risk management projects are informed by gender sensitive data and evidence during the design, implementation and the monitoring and evaluation phases. This information is sourced by collating available secondary data sources (e.g., government census and socio-economic development data), conducting primary data gathering in the project area, and through regular monitoring and evaluation during program implementation. A key obstacle, however, in the development of gender sensitive DRM policies and projects is the lack of sex-disaggregated data (i.e., data that can be separated by men and women). Without disaggregated data, it is difficult to identify, understand and address the different needs of men and women before, during and after a disaster. As gender considerations vary depending on socio-economic conditions and cultural beliefs, sex-disaggregated data is required at all levels. For example, national level disaggregated data is useful, but not sufficient for planning activities at the village level, as gender roles may vary from village to village within a country. The data collected are instrumental in helping identify the needs of men and women to shape the design of early warning systems, emergency preparedness plans, and post-disaster recovery programs among others, and to determine the allocation of funding. Gender-sensitive monitoring and evaluation in DRM programs allow governments and partner organizations to swiftly react to the changing situation in affected areas and enable the involved institutions to make corrections in the program design and implementation plans, re-assess development outcomes and the underlying processes. This can improve the likelihood of achieving the development objectives outlined in the reconstruction programs, and helps the reconstruction partners to understand, effectively respond and shape the dynamic situation on the ground.